Teknologi co-processing : solusi alternatif mereduksi bahan bakar fosil dan gas CO2 di industri semen Indonesia - Yulius Pamungkas (Jurnal Rekayasa Proses, 2010)
Co-processing technology in cement industry is defined as the technology to use wastes such as used oil, scrap tires and other organic wastes in order to reduce fossil fuel consumption. This technology also allows the utilization of material elements contained in the wastes such as alumina, silica and iron to substitute some of raw materials used in cement industry. In Europe, this technology is also known as co-incinerator and being used widely. Hazardous waste disposal in Indonesia is done traditionally using incineration technology. The incineration technology may result toxic ashes that require further treatment before it can be dumped into a secure landfill. Big industries that have combustion reactor system with high temperature such as cement industry, steel industry and power generation could utilize co-processing technology as their long term strategy to reduce both fossil and raw material consumptions. If this technology can be consistently applied in the big industries, it has big potential to reduce the use of fossil fuel (and global warming) and to lower the risk due to traditional hazardous waste disposal. Some keys for successful implementation of the co-processing technology in cement industries include the appropriate selection of feeding method and location; consistency in energy content of the wastes and waste treatments that are compliance with safety and environmental laws. Care should be taken in the use of this technology due to the variation in composition, shape and size of the wastes and its water and impurities content so that these variations would not affect the plant operation stability and the product quality.